2015
DOI: 10.1016/j.cognition.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Children’s understanding of the costs and rewards underlying rational action

Abstract: Humans explain and predict other agents' behavior using mental state concepts, such as beliefs and desires. Computational and developmental evidence suggest that such inferences are enabled by a principle of rational action: the expectation that agents act efficiently, within situational constraints, to achieve their goals. Here we propose that the expectation of rational action is instantiated by a naïve utility calculus sensitive to both agent-constant and agent-specific aspects of costs and rewards associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 34 publications
5
131
1
Order By: Relevance
“…That is, teachers may act to increase learners’ perceived rewards and decrease their perceived costs. Recent work has formalized this intuition to suggest that people reason about their own and others’ goal‐directed actions via a naive utility calculus (Jara‐Ettinger et al., ), and a number of recent empirical studies shows that even young children reason about others’ actions in ways that are consistent with predictions of utility‐based models (e.g., Bridgers, et al., ; Jara‐Ettinger et al., ). The current work provides indirect support for the idea that children reason about expected rewards and costs.…”
Section: Discussionmentioning
confidence: 99%
“…That is, teachers may act to increase learners’ perceived rewards and decrease their perceived costs. Recent work has formalized this intuition to suggest that people reason about their own and others’ goal‐directed actions via a naive utility calculus (Jara‐Ettinger et al., ), and a number of recent empirical studies shows that even young children reason about others’ actions in ways that are consistent with predictions of utility‐based models (e.g., Bridgers, et al., ; Jara‐Ettinger et al., ). The current work provides indirect support for the idea that children reason about expected rewards and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent models have considerably extended this basic premise to capture causal relations between other kinds of mental states. For example: Greg’s choices additionally depend on (what he believes about) the costs of his actions [11]; his beliefs update in response to new evidence [7]; his actions are influenced by his habits [12]; and so on. A hierarchical Bayesian model of this intuitive causal theory can explain both observers’ forward inferences (predicting Greg’s actions given his beliefs and desires) and inverse inferences (inferring Greg’s beliefs and desires given his actions) [10].…”
Section: Situating Emotion Concepts Within An Intuitive Theory Of Mindmentioning
confidence: 99%
“…In one series of experiments [57] we found that when five-year-olds learn an agent's costs and choices, they infer a reward function that guarantees that the agent maximized her utilities. We showed children a puppet who chooses crackers over cookies when both items are equidistant, but cookies over crackers when the cookies are closer (Figure 4a).…”
Section: Evidence For the Naïve Utility Calculusmentioning
confidence: 99%